African Statistical Yearbook 2012 - United Nations (United Nations, 2013)
The Yearbook series is a result of collaborative efforts by major African regional organizations to set up a joint data collection mechanism of socioeconomic data on African countries, as well as the development of a harmonized database. It seeks to promote wider use of country data, reduce costs, significantly improve the availability and quality of the data, and lead to better monitoring of development initiatives on the continent. The data in this issue of the Yearbook are arranged generally for the years 2003-2011, or for the last eight years for which data are available. It is published in a single volume consisting of two parts: a set of summary tables followed by country profiles.